Misfitting Elliptic Elastic Inhomogeneity Problem in Perfectly Anisotropic Media - Bhargava, R.R.; Saxena, H.S. (Engineering Transactions, 1978)
The problem considered in this paper is that of a misfitting elliptic inclusion in an infinite elastic region. The stresses develop because of the misfit. The inclusion and the outside material, called the matrix, are both of homogeneous and perfectly anisotropic materials. Further, the elastic properties of the two materials may differ. The complex variable technique is employed to evaluate two sets of complex potential functions (jk): k = 1, 2, 3, one for the inhomogeneity and another for the outside region, which give the elastic field every where.